A STUDY ON THE CHARACTERISTICS OF MEDICAL ABORTION AT ≤ 9 WEEKS OF GESTATION IN WOMEN WITH A PREVIOUS CESAREAN SECTION AT BINH DUONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: In recent years, the rate of cesarean section in Vietnam has shown a rising trend, resulting in an increasing number of women of reproductive age with a previous uterine scar [1]. Concurrently, the prevalence of unintended pregnancy remains considerable; several studies have reported that unintended pregnancies account for up to 53.6% of all pregnancy terminations [2]. Medical abortion is a safe and minimally invasive method for terminating early intrauterine pregnancy and is recommended by the World Health Organization for use in early gestation. However, among women with a previous cesarean section, the risk of complications—such as uterine rupture, hemorrhage, retained products of conception, or the need for surgical intervention—may be higher compared to women without a uterine scar. At Binh Duong General Hospital, a substantial number of women seek pregnancy termination each year; nevertheless, no study has specifically addressed this issue in the local context. The absence of locally derived data may pose challenges for clinicians in accurately counselling patients on success rates, anticipated adverse effects, and individualised risk prognostication based on the distinctive demographic and clinical characteristics of the regional population. Objectives: To describe the characteristics of cases undergoing medical abortion at ≤ 9 weeks of gestation among women with a history of cesarean section at Binh Duong General Hospital. Materials and methods: A cross-sectional descriptive study was conducted. The study population included pregnant women with a history of cesarean delivery and a gestational age of ≤ 9 weeks who presented to the hospital for pregnancy termination. Results: The mean age of participants was 33.22 ± 5.97 years, ranging from 21 to 48 years. The majority resided in urban areas (60 cases, 75.9%). Women with one prior cesarean section constituted the most significant proportion (47 cases, 59.5%). Twenty-three participants (29.1%) had undergone at least one previous abortion. The mean gestational age was 6.10 ± 1.22 weeks. The mean interval from the onset of abdominal pain to the occurrence of vaginal bleeding was 55.95 ± 21.23 minutes. The overall success rate of medical abortion was 89.9% (71 cases).Conclusion: Medical abortion in women with a prior cesarean section and a gestational age of ≤ 9 weeks demonstrated a high success rate (89.9%).
Keywords: medical abortion; cesarean section; mifepristone; misoprostol.